2018
DOI: 10.5688/ajpe6771
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pharmacotherapy Instruction to the 2009 and 2016 ACCP Toolkit Recommendations

Abstract: Methods.A survey was sent to representatives at US PharmD programs. The survey consisted of questions pertaining to: pharmacotherapy credit-hours; contact time spent for each therapeutic subject area; and pedagogical methods used. Data were analyzed using descriptive statistics. Results.Representatives from 75/129 PharmD programs responded (response rate 58%). A median of 23 credit-hours were devoted to required pharmacotherapy. Infectious diseases and cardiology were taught with the greatest number of contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Previous studies over the last few decades have consistently shown that the extent to which geriatric content is taught at US schools of pharmacy has not kept pace with the expanding population of older adults [ 18 , 19 , 20 ]. A recent survey of American schools and colleges of pharmacy found that respondent schools spent a median of six contact hours teaching geriatric pharmacotherapy [ 21 ]. As a concept, deprescribing first appeared in the American College of Clinical Pharmacy (ACCP) Pharmacotherapy Didactic Toolkit in the recently published 2019 update as a Tier 1 topic (highest priority) [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies over the last few decades have consistently shown that the extent to which geriatric content is taught at US schools of pharmacy has not kept pace with the expanding population of older adults [ 18 , 19 , 20 ]. A recent survey of American schools and colleges of pharmacy found that respondent schools spent a median of six contact hours teaching geriatric pharmacotherapy [ 21 ]. As a concept, deprescribing first appeared in the American College of Clinical Pharmacy (ACCP) Pharmacotherapy Didactic Toolkit in the recently published 2019 update as a Tier 1 topic (highest priority) [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies demonstrate that improvements in pharmacy and medical ID education are warranted. Although ID had the highest number of devoted contact hours (median 36; interquartile range, 29–60) [25], there were major concerns regarding the lack of time needed to cover the necessary ID materials by ID PharmD faculty [26]. Furthermore, there were considerable differences in the level of integration, pedagogical methods, and depth of antimicrobial stewardship topics delivered in colleges of pharmacy [14, 26].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of malignant tumors named cancers is increasing by years, with the gradually accelerated pace of human production and life . At present, the main techniques of treating cancers such as chemotherapy, radiotherapy, surgery, and other medical methods are conventionally utilized, especially pharmacotherapy . However, in the course of drug therapy, in general, only a small amount of drugs reach to the focal site due to the fact that the drugs spread throughout the whole body through the blood circulation during killing tumor cells via pharmacotherapy, which eventually results in the low drug utilization and the damage to normal cells .…”
Section: Introductionmentioning
confidence: 99%